The rise and fall of the EU's constitutional treaty - Laursen, Finn (Dordrecht, 2008)
"This book analyses the EU's Constitutional Treaty, which emerged in draft form from the European Convention in the summer of 2003 and which was finalised by an Intergovernmental Conference (IGC) in June 2004. It describes the main novelties of the treaty and looks at policies of important actors, Member States and Community actors (the Commission and European Parliament) and the roles played by the Convention and the Italian and Irish Presidencies during the process of deliberation and negotiation that produced the treaty. It further studies the failure of ratification in France and the Netherlands and the implications for the process of European integration of this failure. It finally touches on the question whether a constitutional equilibrium has been reached. Since the new Lisbon Treaty negotiated in 2007 contains much of what was in the Constitutional Treaty the analyses of the book remain pertinent for this latest EU treaty. "